Multi‐Phase Heterostructure of CoNiP/CoxP for Enhanced Hydrogen Evolution Under Alkaline and Seawater Conditions by Promoting H2O Dissociation - Liu, Dong; Ai, Haoqiang; Chen, Mingpeng; Zhou, Pengfei; Li, Bowen; Liu, Di; Du, Xinyu; Lo, Kin Ho; Ng, Kar‐Wei; Wang, Shuang‐Peng; Chen, Shi; Xing, Guichuan; et al. (Small (Weinheim an der Bergstrasse, Germany), 2021)
Hydrogen evolution reaction (HER) is a key step for electrochemical energy conversion and storage. Developing well defined nanostructures as noble‐metal‐free electrocatalysts for HER is promising for the application of hydrogen technology. Herein, it is reported that 3D porous hierarchical CoNiP/CoxP multi‐phase heterostructure on Ni foam via an electrodeposition method followed by phosphorization exhibits ultra‐highly catalytic activity for HER. The optimized CoNiP/CoxP multi‐phase heterostructure achieves an excellent HER performance with an ultralow overpotential of 36 mV at 10 mA cm−2, superior to commercial Pt/C. Importantly, the multi‐phase heterostructure shows exceptional stability as confirmed by the long‐term potential cycles (30,000 cycles) and extended electrocatalysis (up to 500 h) in alkaline solution and natural seawater. Experimental characterizations and DFT calculations demonstrate that the strong electronic interaction at the heterointerface of CoNiP/CoP is achieved via the electron transfer from CoNiP to the heterointerface, which directly promotes the dissociation of water at heterointerface and desorption of hydrogen on CoNiP. These findings may provide deep understanding on the HER mechanism of heterostructure electrocatalysts and guidance on the design of earth‐abundant, cost‐effective electrocatalysts with superior HER activity for practical applications. The CoNiP/CoxP multi‐phase heterostructure with 3D porous hierarchical morphology optimizes the electronic structure, thereby reducing the energy barrier for water dissociation, increasing the adsorption energy of H2O and OH−, and achieving near‐zero Gibbs free energy of hydrogen adsorption. A novel HER mechanism on CoNiP/CoxP multi‐phase heterostructure is proposed to be the water dissociation on heterointerface and H2 production on CoNiP.